Anna Rice, John Southwell celebrate 95th birthdays - Cinelli, Arlene (Raton, New Mexico Raton Range, 1974)
Newspaper Article on the 95th birthdays of Anna Rice and John Southwell.
Master list item #: 23
File location is in the Raton File Cabinet
Keywords: Rice, Anna; Southwell, John; Lackey, Howard; Lackey, (Mrs.); Gurule, Robert; King, Bruce; Daily Range; International State Bank; Local History; Biography; Life and Customs; Birthday; Celebration; Raton, New Mexico